Joe Celko's SQL puzzles and answers: - Celko, Joe (Epsevier, 2007)
In this complete revision and expansion of his first SQL Puzzles book, Joe Celko challenges you with his trickiest puzzlesand then helps solve them with a variety of solutions and explanations. Joe demonstrates the thought processes that are involved in attacking a problem from an SQL perspective to help advanced database programmers solve the puzzles you frequently face. These techniques not only help with the puzzle at hand, but help develop the mindset needed to solve the many difficult SQL puzzles you face every day. Of course, part of the fun is to see whether or not you can write better solutions than Joes.